2015
DOI: 10.1002/2014ja020855
|View full text |Cite
|
Sign up to set email alerts
|

Polytropic index of central plasma sheet ions based on MHD Bernoulli integral

Abstract: This paper uses the data of Cluster from 2001 to 2009 to study the polytropic processes of central plasma sheet (CPS) ions. We first adopt the approach of MHD Bernoulli integral (MBI) to identify homogeneous streamflow tubes (quasi-invariant MBI regions) and then calculate the polytropic index of ions for those streamflow tubes whose outward electromagnetic energy ratios δ < 0.05. The central plasma sheet is actually a complicated system, which comprises many streamflow tubes with different polytropic relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…This result indicates a possible connection to the flow-braking region which is usually found at similar downtail distances (see, e.g. Baumjohann and Glassmeier, 1984, Shiokawa et al, 1997, Dubyagin et al, 2010, and Yao et al, 2012 for observations and possible mechanisms). To study possible hemispheric differences in the Y and Z directions of the tail, the orbit-wise analysis is carried out in the relevant hemispheres.…”
Section: Radial and Hemispheric Dependencesupporting
confidence: 63%
See 3 more Smart Citations
“…This result indicates a possible connection to the flow-braking region which is usually found at similar downtail distances (see, e.g. Baumjohann and Glassmeier, 1984, Shiokawa et al, 1997, Dubyagin et al, 2010, and Yao et al, 2012 for observations and possible mechanisms). To study possible hemispheric differences in the Y and Z directions of the tail, the orbit-wise analysis is carried out in the relevant hemispheres.…”
Section: Radial and Hemispheric Dependencesupporting
confidence: 63%
“…Consequently, no shift of the distribution towards lower polytropic indices as reported by previous works can be observed (Baumjohann and Paschmann, 1989;Goertz and Baumjohann, 1991). Instead, if analyzed individually, both active-and quiet-time distributions are similar and cover a wide range of polytropic indices (e.g., Pang et al, 2015). It should be noted that there is a small portion of events (< 1 %) in the ranges γ → 0 and γ → 4.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…Thus, the adiabatic assumption of plasma sheet ions is not appropriate. Pang et al (2015aPang et al ( , 2015b adopted the approach of MHD Bernoulli integral and found that the polytropic index of background plasma sheet ions have a wide distribution around γ~1.0. Pang et al (2015aPang et al ( , 2015b adopted the approach of MHD Bernoulli integral and found that the polytropic index of background plasma sheet ions have a wide distribution around γ~1.0.…”
Section: 1029/2019ja026681mentioning
confidence: 99%